2017
DOI: 10.3892/etm.2017.5249
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of oxidative damage on cardiomyocyte differentiation from Wharton's jelly‑derived mesenchymal stem cells

Abstract: Ischemic heart diseases are a serious health problem worldwide. The transplantation of mesenchymal stem cells (MSCs) has been investigated in numerous clinical trials on various other diseases due to the self-renewal capacity of these cells and their potential to differentiate into a variety of cell types. The presence of excess reactive oxygen species in injured myocardium causes cardiac dysfunction and leads to inefficient repair of the heart. The poor outcomes of stem cell transplantation have been suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Here, we found that in both cell populations, H 2 O 2 not only inhibited cell proliferation in a dose-dependent fashion, but it also affected the persistence of the anti-proliferative effect after the end of exposure (up to 48 or 72 h) in a manner that was dependent upon the duration (1 or 2 h) of the treatment itself. These results are coherent with the reduction of cell vitality observed in hWJ-MSCs 43 - 45 and hASCs 39 , 42 treated with higher concentrations of H 2 O 2 (until 2000 μM) but at low subcultured passages. We also observed a growth slowdown of cells treated with H 2 O 2 400 μM, and a cell inability to re-plate.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Here, we found that in both cell populations, H 2 O 2 not only inhibited cell proliferation in a dose-dependent fashion, but it also affected the persistence of the anti-proliferative effect after the end of exposure (up to 48 or 72 h) in a manner that was dependent upon the duration (1 or 2 h) of the treatment itself. These results are coherent with the reduction of cell vitality observed in hWJ-MSCs 43 - 45 and hASCs 39 , 42 treated with higher concentrations of H 2 O 2 (until 2000 μM) but at low subcultured passages. We also observed a growth slowdown of cells treated with H 2 O 2 400 μM, and a cell inability to re-plate.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, H 2 O 2 treatment provokes DNA breaks 41 , raises SA β-Gal positive cells 42 , alters the expression of senescent marker genes, as well as p53 , p21 , mitogen-activated protein kinase 14 ( MAPK14 , alias p38 ) and sirtuin 1 ( SIRT1 ) 38 , 39 , 42 , and increases apoptosis with a decline of pro-survival gene expression 38 . It has been recently shown that also human Wharton's Jelly-derived MSCs (hWJ-MSCs) treated with H 2 O 2 undergo premature senescence at early culture passages: these cells show typical changes in morphology 43 , slow their proliferation 44 , 45 , result positive for SA β-Gal 43 , 44 , express typical senescence 43 and pro-apoptotic gene markers, while displaying a down-regulation of survival genes 44 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cords were collected from mothers with normal labor as previously described (28). All participants have read and signed the informed consent, which was approved by the Mahidol University Institutional Review Board (protocol no.…”
Section: Isolation and Culture Of Wj-mscsmentioning
confidence: 99%
“…WJ-MSCs in all experiments were performed as previously described (28). WJ-MSCs were characterized according to the minimal criteria for defining MSCs, stated by the International Society for Cellular Therapy (29).…”
Section: Wj-mscs Characterizationmentioning
confidence: 99%
See 1 more Smart Citation